Assessment of the statokinetic stability of athletes in various sports - A.S. , Nazarenko; F.A. , Mavliev; V.R. , Karfik (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the level and identify neuromotor mechanisms of statokinetic stability regulation in elite athletes across different types of sporting activity. Methods and structure of the study. The research was conducted at the Research Institute of Physical Culture and Sport at Volga Region State University of Physical Culture, Sport and Tourism. A total of 227 male subjects actively engaged in sport, with at least 9 years of experience and sporting qualifications ranging from second adult rank to Master of Sport of the Russian Federation, were examined. Statokinetic stability was assessed using a stabilometric platform with biofeedback in a state of relative rest. Results and conclusions. A comparison of statokinetic stability indicators was conducted among elite athletes representing cyclic, precision, and situational sports, as well as non-athletes. Athletes in cyclic sports demonstrated higher mean linear velocities of centre of pressure oscillation and greater rates of change in the statokinesiogram area compared with representatives of precision and situational sports. Simultaneously, they exhibited the lowest values of the integrative “balance function quality” indicator. This is explained by more refined regulation of the statokinetic system and lower centre of pressure oscillation velocity in athletes from precision and situational sports.